Obstacles to integrating students with special needs into regular schools from the viewpoint of primary education teachers - a field study in the province of M’sila - hadi, souheyr; alitoudert, nassima (Journal of Social Sciences and Humanities, 2023)
The current study aimed to identify the obstacles to the integration of students with special needs in regular schools according to the point of view of primary education teachers, and to achieve this, the study was conducted on a sample of (65) teachers from primary schools in the province of M'sila, who were randomly selected and applied to them a questionnaire obstacles to the integration of students with special needs from the preparation of Bahri Saber and Kharmoush Mona (2022), which consists of (32) items, and for statistical processing of data, the researchers relied on the statistical package program for social sciences Spss. The results showed that the obstacles to the integration of students with special needs in regular schools according to the point of view of primary education teachers, include all levels of the teacher, colleagues, school, student with special needs, but the school is the first obstacle, then the second obstacle teacher, followed by the third obstacle, which is related to colleagues, and the fourth obstacle is the student with special needs. The study recommended the need to activate the regulations and laws governing integration, and to review the curricula to suit the characteristics of students with special needs, and work to qualify teachers in regular schools according to b